Electrocardiographic changes after alcohol septal ablation in hypertrophic obstructive cardiomyopathy. Issue 3 (1st September 1998) - Kazmierczak, J; Kornacewicz-Jach, Z; Kisly, M; Gil, R; Wojtarowicz, A
Abstract : Objective: To report acute and mid-term electrocardiographic changes in patients with hypertrophic obstructive cardiomyopathy (HOCM) after alcohol ablation of the first large septal branch of the left anterior descending coronary artery; and to relate electrocardiographic data with the left ventricular outflow tract pressure gradients. Patients: Nine consecutive symptomatic patients with HOCM (mean (SD) age 45 (12) years). Methods: Analysis of baseline and postprocedure ECGs and 24 hour ambulatory monitoring (up to six months). ECG data were related to left ventricular outflow tract pressure gradients. Results: One patient developed complete atrioventricular block requiring permanent pacing. The PR interval was significantly prolonged up to third month after ablation. Immediately after the procedure all patients developed right bundle branch block. At the sixth month of follow up, right bundle branch block was present in four patients. New anterior ST elevation developed immediately after ablation in five of the nine patients, and new Q waves in four. The QRS duration was significantly prolonged immediately after ablation and during follow up. There was significant but transient prolongation of QT-mean and QTc-mean intervals. QT dispersion, QTc dispersion, and JTc-mean interval were not affected. JT and JTc dispersions were transiently prolonged. No serious ventricular arrhythmias were recorded during Holter monitoring, either before or after the procedure. There were no significant correlations between the left ventricular outflow tract pressure gradient and QTc, QT-d, QTc-d, JTc, JT-d, JTc-d, or QRS duration before and after ablation. Conclusions: Alcohol septal ablation for HOCM induces significant changes in the resting ECG in most patients, despite the occlusion of a relatively small artery. The changes include new Q waves, new bundle branch block, transient anterior ST segment elevation, atrioventricular block, and transient prolongation of QT interval.